Family caps, abortion, and women of color research connection and political rejection - Camasso, Michael (Oxford : Oxford University Press, 2007)
Aimed at professionals, academics and researchers, lawyers, as well as a general readership, this title examines areas such as reforming welfare with family Caps, family Caps and non-marital births, testing family Cap theory and re-authorization.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Welfare recipients -- Government policy -- United States; Family size -- Government policy -- United States; Low-income single mothers -- Government policy -- United States; Public welfare -- United States; Public welfare -- Law and legislation -- United States; Abortion -- United States